Evaluation of immediate and delayed surgery for pathological fracture due to unicameral bone cysts in children. (2020) - Chen, Xin; Chen, Kai; Su, Yuxi
Abstract: Purpose: Unicameral bone cysts (UBCs) are most often found when accompanied by a pathological fracture. In these cases, the doctor must determine the optimal timing for the surgery. The purpose of this study was to evaluate the outcome of immediate surgery as compared with delayed surgery in paediatric pathological fractures due to UBCs. Methods: This retrospective study assessed the medical records of 65 patients between January 2012 and September 2016. Group A included 34 patients who underwent immediate surgery, including curettage, demineralized bone matrix and fixation with elastic stable intramedullary nailing. Group B included 31 patients who underwent the same surgery several months later. The outcome evaluations included the radiological changes, brace fixation time, cyst healing time, at the first-, third- and sixth month, and final visit. Results: The mean brace fixation time was 26.3 days (sd 5.7) for group A and 53.8 days (sd .1) for group B (p = 0.012). According to radiological evaluations, 3/34 patients in group A and 5/31 in group B had recurrence after the first surgery. A second surgery was performed in all cases of recurrence, and all fractures were healed at the last visit. There was no significant difference in the recurrence rate between the two groups (p = 0.4631), and healing times were also similar (p = 0.6033). Conclusion: Both the immediate and delayed surgery were safe for the treatment of UBCs with fractures. We suggest immediate surgery for shorter fixation time and early activity. Level of evidence: IV